PENGARUH PARTISIPASI PUBLIK DALAM PROSES PEMBENTUKAN UNDANG-UNDANG DI ERA DIGITAL: STUDI KASUS PADA UU CIPTA KERJA - Sukadi, Muhammad; Nuriskandar, Lalu Hendri (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2024)
This study aims to analyze the influence of public participation in the process of forming laws in the digital era, with a case study on the Job Creation Law. In the digital era, technology has opened up new opportunities for the public to be more actively involved in the legislative process through various digital platforms. However, although access to the process of forming laws is increasingly easy, the quality and impact of public participation are often still questionable. This study uses a qualitative approach with a case study method to explore the extent to which public participation through digital media influences the process of forming the Job Creation Law. Data were collected through document analysis, in-depth interviews, and participant observation. The results of the study show that although digital technology has increased the amount of public participation, not all public input is adequately considered in the decision-making process. In addition, challenges such as digital exclusion and personal data protection are significant obstacles to increasing the effectiveness of participation. In conclusion, the digital era offers great opportunities to strengthen public participation in the process of forming laws, but improvements are needed in public engagement mechanisms, increased transparency, and privacy protection to ensure that such participation truly has an impact. Recommendations provided include the development of a more inclusive participation platform, increased transparency in the processing of public input, and stricter enforcement of privacy policies. Keywords: public participation, digital era, law formation, Job Creation Law, digital technology.